Tracking biological invasions in space and time: elucidating the invasive history of the green alga Codium fragile using old DNA - Provan, Jim; Booth, David; Todd, Nicola; Beatty, Gemma; Maggs, Christine (Diversity and Distributions, 2008)
With the advent of 'ancient DNA' studies on preserved material of extant and extinct species, museums and herbaria now represent an important although still underutilized resource in molecular ecology. The ability to obtain sequence data from archived specimens can reveal the recent history of cryptic species and introductions. We have analysed extant and herbarium samples of the highly invasive green alga Codium fragile, many over 100 years old, to identify cryptic accessions of the invasive strain known as C. fragile ssp. tomentosoides, which can be identified by a unique haplotype. Molecular characterization of specimens previously identified as native in various regions shows that the invasive tomentosoides strain has been colonizing new habitats across the world for longer than records indicate, in some cases nearly 100 years before it was noticed. It can now be found in the ranges of all the other native haplotypes detected, several of which correspond to recognized subspecies. Within regions in the southern hemisphere there was a greater diversity of haplotypes than in the northern hemisphere, probably as a result of dispersal by the Antarctic Circumpolar Current. The findings of this study highlight the importance of herbaria in preserving contemporaneous records of invasions as they occur, especially when invasive taxa are cryptic.